RECOARCTATION AFTER SURGICAL CORRECTION OF COARCTATION OF THE AORTA IN CHILDREN AND ADOLESCENTS - Kuzmanović, Milica (Medicinski podmladak, 2025)
Introduction: Coarctation of the aorta (CoA) is a narrowing of the thoracic aorta, most often localized at the junction of ductus arteriosus. Data on risk factors for the development of recoarctation remain contradictory in literature. The aim: To determine the frequency of recoarctation and to identify risk factors for the recoarctation after surgical correction of CoA. Material and methods: The research included 94 patients who underwent surgery for coarctation of the aorta from 2012 to 2017. Demographic and clinical characteristics, preoperative, intraoperative, postoperative and echocardiographic parameters were observed. Pressure gradient over 25 mmHg immediately after operation is considered predictоr for recoarctation of the aorta. The data was processed using methods of descriptive and analytical statistics. Results: The median age at the time of surgery was 2 months (4 days-19 years). The dominant technique was extended end-to-end anastomosis (90.4%). Kaplan Meier survival analysis showed higher incidence of recoarctation in the group of patients with immediate postoperative gradient >25 mmHg (p<0.001). Also, Cox logistic regression showed higher immediate postoperative gradient to be a predictor (HR 4.57, p=0.009, 95% CI 1.47 -14.22). After correction for other cofactors, including sex, genetic syndrome, small body weight, administration of prostaglandine E1, presence of bicuspid aortic valve, surgical technique, it was shown that group of patients with higher immediate postoperative gradient has 4-fold higher probability for recoarctation (HR 4.37, p=0.035, 95% CI 1,11 -17,16) . Conclusion: Immediate postoperative pressure gradient > 25 mmHg is an independent predictor for recoarctation after surgical correction of the coarctation of the aorta.